The Evening News - Hailey, Arthur (London Corgi Books, 1990)
Long-time rivals, news figures Sloane and Partridge, once in love with the same woman, become involved in the crisis of drug-financed terrorism imported to America from Peru.
Keywords: Television journalists -- Kidnapping -- Terrorists